Erratum: DANKITTIPAKUL, P., JOCQUÉ, R. & SINGTRIPOP, T. (2012) Systematics and biogeography of the spider genus Mallinella Strand, 1906, with descriptions of new species and new genera from Southeast Asia (Araneae, Zodariidae). Zootaxa, 3369, 1–327. - Dankittipakul, P.; Jocqué, R.; Singtripop, T. (Zootaxa, 2012)
(Erratum)